Code-Mixing in Denny Sumargo and Jessica Iskandar Conversation on Youtube - Anita , Ni Ketut Chandra; Maharani, Putu Devi; Sulatra , I Komang (Journal of Language and Applied Linguistics, 2024)
This study is concerned with analyzing the code mixing found in CURHAT BANG Denny Sumargo YouTube channel. This study aims to identify the types and the reasons of code mixing found on CURHAT BANG Denny Sumargo YouTube channel. This study applied the theory proposed by Hoffman (1991) to analyze the data. The data of this study were taken from one video entitled “Aku Dan El Barack Menangis Bareng Di Garasi Aku Udah Gak Percaya Cinta Lagi”. In realizing the objectives, this study applied descriptive qualitative and quantitative methods to analyze the data. Then this study used the observation method and noted taking technique to collect the data. This study found three types of code mixing, and the most frequent type found in this study is intra-sentential code mixing. This study found five reasons of code mixing, and expressing group identity is the most frequently used in this conversation. The data of code mixing in this study were taken from the utterances of two participants, those are between Denny Sumargo and Jessica Iskandar